2016
DOI: 10.1074/jbc.m115.681478
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Defenses of Francisella tularensis Modulate Macrophage Function and Production of Proinflammatory Cytokines

Abstract: Francisella tularensis, the causative agent of a fatal human disease known as tularemia, has been used in the bioweapon programs of several countries in the past, and now it is considered a potential bioterror agent. Extreme infectivity and virulence of F. tularensis is due to its ability to evade immune detection and to suppress the host's innate immune responses. However, Francisella-encoded factors and mechanisms responsible for causing immune suppression are not completely understood. Macrophages and neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 73 publications
(82 reference statements)
1
30
0
Order By: Relevance
“…While oxidative stress (ROS production) is well known to be a precursor to cytotoxicity and genotoxicity generally, which could in turn affect innate immune functions, ROS production also plays an important role in killing of intracellular bacteria, including FT [7275]. Indeed, FT has been shown to downregulate host cellular ROS responses and to produce superoxide disumtases in order to provide protection against ROS within macrophages [7375].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While oxidative stress (ROS production) is well known to be a precursor to cytotoxicity and genotoxicity generally, which could in turn affect innate immune functions, ROS production also plays an important role in killing of intracellular bacteria, including FT [7275]. Indeed, FT has been shown to downregulate host cellular ROS responses and to produce superoxide disumtases in order to provide protection against ROS within macrophages [7375].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, FT has been shown to downregulate host cellular ROS responses and to produce superoxide disumtases in order to provide protection against ROS within macrophages [7375]. It is thus possible that changes in ROS production caused by ENM exposure could alter FT killing by macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…First, F. tularensis surface polysaccharidic O-antigen acts as a shield against ubiquitinylation and subsequent xenophagic recognition during infection of cultured murine macrophages[24]. Second, antioxidant superoxide dismutase enzymes of F. tularensis inhibit ROS-mediated induction of xenophagy and LC3-associated phagocytosis (LAP) during infection of cultured murine macrophages[25]. In addition, F. tularensis exploits an ATG5-independent autophagy pathway in fibroblasts and macrophages to obtain nutrients released from degraded cellular constituents to promote its replication[26].…”
Section: Xenophagy Beyond M Tuberculosis As Revealed By Cell Culturementioning
confidence: 99%
“…Previously, it has been demonstrated that the up-regulation of p38, IkB and c-Jun occurs following infection of murine macrophages with F. tularensis strain LVS [15]. In addition, it has been demonstrated that the uptake of Francisella novicida by macrophages is dependent upon ERK activation, and modulation of the MAPK pathways is important for intracellular survival of F. tularensis LVS [23, 24]. Furthermore, within an in-vivo setting it was found that the inhibition of GSK3B (a serine/threonine protein kinase) with lithium chloride significantly reduces the production of pro-inflammatory cytokines such as IFN-γ, IL-12p40, and TNF-α in F. tularensis LVS-infected mice, and increases survival from 60 % in untreated mice to 90 % following treatment [25].…”
Section: Introductionmentioning
confidence: 99%